GREEN TECHNOLOGIES AND THE FIGHT AGAINST CLIMATE CHANGE (Web of Discoveries: Journal of Analysis and Inventions, 2025)
Green technologies are pivotal in addressing the global challenges posed by climate change. As the world grapples with rising temperatures, extreme weather events, and ecosystem degradation, the need for sustainable solutions has never been more urgent. This paper explores the role of green technologies in mitigating the effects of climate change, emphasizing renewable energy, energy efficiency, sustainable agriculture, and carbon capture technologies. Renewable energy sources such as solar, wind, and hydropower offer cleaner alternatives to fossil fuels, significantly reducing greenhouse gas emissions. Energy efficiency innovations in various sectors, from transportation to industrial production, help optimize resource use and minimize carbon footprints. Sustainable agricultural practices, including precision farming and agroforestry, not only enhance food security but also contribute to carbon sequestration. Additionally, advancements in carbon capture and storage (CCS) technologies present promising solutions for reducing atmospheric CO2 concentrations. Despite the progress, challenges remain in the widespread adoption of these technologies due to economic, political, and technological barriers. The paper concludes by emphasizing the need for enhanced global collaboration, research, and policy frameworks to accelerate the transition to a green economy, ensuring that green technologies play a central role in mitigating climate change and achieving long-term environmental sustainability.